A Positive Feedback Loop Between c-Myc Upregulation, Glycolytic Shift, and Histone Acetylation Enhances Cancer Stem Cell-like Property and Tumorigenicity of Cr(VI)-transformed Cells. (11th June 2020) - Clementino, Marco; Xie, Jie; Yang, Ping; Li, Yunfei; Lin, Hsuan-Pei; Fenske, William K; Tao, Hua; Kondo, Kazuya; Yang, Chengfeng; Wang, Zhishan
Abstract: Chronic hexavalent chromium [Cr(VI)] exposure causes lung cancer and other types of cancer; however, the mechanism of Cr(VI) carcinogenesis remains to be clearly defined. Our recent study showed that chronic Cr(VI) exposure upregulates the proto oncogene c-Myc expression, which contributes significantly to Cr(VI)-induced cell transformation, cancer stem cell (CSC)-like property and tumorigenesis. c-Myc is a master regulator of cancer cell abnormal metabolism and accumulating evidence suggests that metabolism dysregulation plays an important role in both cancer development and progression. However, little is known about the role of metabolism dysregulation in Cr(VI) carcinogenesis. This study was performed to investigate the potential role and mechanism of metabolism dysregulation in Cr(VI) carcinogenesis. It was found that Cr(VI)-transformed cells display glycolytic shift, which depends on the upregulation of c-Myc. The glycolytic shift in Cr(VI)-transformed cells led to increased production of acetyl coenzyme A (acetyl-CoA) and elevation of histone acetylation. This, in turn, upregulated the expression of an acetyl-CoA producing key enzyme ATP citrate lyase and c-Myc, forming a positive feedback loop between the upregulation of c-Myc expression, glycolytic shift and increased histone acetylation. It was further determined that glucose depletion not only reverses the glycolytic shift in Cr(VI)-transformed cells, but also significantly reduces their growth, CSC-like property and tumorigenicity. These findings indicate that glycolytic shift plays an important role in maintaining malignant phenotypes of Cr(VI)-transformed cells, suggesting that metabolism dysregulation is critically involved in Cr(VI) carcinogenesis.